PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS3 PROFESSIONAL DALAM PEMBELAJARAN IPA BERBASIS INTEGRASI ISLAM-SAINS DI SD/MI KELAS 5 - Fitri Yuliawati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to: (1) Developing learning media based on adobe flash cs3 professional in science teaching based on integration of Islam-science in SD/MI class 5, and (2) Know the media feasibility of the development of adobe flash based learning media cs3 professional in science-based learning integration of Islam-science in SD/MI class 5 as a medium of learning. The type of research used is Research and Development. The design of this research refers to the ADDIE development model which includes 5 stages: Analysis, Design, Development, Implementation and Evaluation. Instruments used to collect data in this study are the assessment sheet for material experts and media experts. Based on the result of research, it can be concluded that: (1) It has successfully developed adobe flash-based learning media cs3 professional in science-based learning integration of Islam in SD/MI 5th grade using the ADDIE development model which includes 5 stages: Analysis, Design, Development, Implementation, and Evaluation, (2) Based on the assessment of material expert is Very Good (VG) with average score 65 and based on media expert’s appraisal is Good (G) with score 55 then learning media based adobe flash cs3 professional in science learning based on islamscience integration in SD/MI grade 5 is suitable for learning media.